2008
DOI: 10.1111/j.1460-9568.2008.06271.x
|View full text |Cite
|
Sign up to set email alerts
|

Expertise in dance modulates alpha/beta event‐related desynchronization during action observation

Abstract: We presented professional dancers and non-dancers with videos of two movement styles, dance movements and everyday movements. Participants were asked to indicate by a button press to which category a movement belonged. We computed event-related desynchronization (ERD) in alpha and beta frequency bands between 7.5 and 25 Hz relative to a visual baseline condition. Power in alpha and lower beta frequency bands was significantly reduced if dancers watched dance movements but not if non-dancers watched dance movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
169
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 31 publications
18
169
2
Order By: Relevance
“…First, beta rhythms, together with mu rhythms, are typically considered to be electrophysiological markers of motor-related activity in the brain. Many studies have found both mu and beta suppression when people perform actions, observe actions or imagine themselves performing actions (Jurkiewicz et al, 2006;McFarland et al, 2000aMcFarland et al, , 2000bNeuper et al, 2006;Orgs et al, 2008;Pfurtscheller and Lopes da Silva, 1999;Pfurtscheller et al, 2006;Pineda, 2005). Suppression of beta rhythms has also been reported when people understand action language compared to abstract language (Moreno et al, 2013), or action language referring to animals compared to action language referring to humans (van Elk et al, 2010).…”
Section: Congruence Effects In Action Languagementioning
confidence: 99%
“…First, beta rhythms, together with mu rhythms, are typically considered to be electrophysiological markers of motor-related activity in the brain. Many studies have found both mu and beta suppression when people perform actions, observe actions or imagine themselves performing actions (Jurkiewicz et al, 2006;McFarland et al, 2000aMcFarland et al, , 2000bNeuper et al, 2006;Orgs et al, 2008;Pfurtscheller and Lopes da Silva, 1999;Pfurtscheller et al, 2006;Pineda, 2005). Suppression of beta rhythms has also been reported when people understand action language compared to abstract language (Moreno et al, 2013), or action language referring to animals compared to action language referring to humans (van Elk et al, 2010).…”
Section: Congruence Effects In Action Languagementioning
confidence: 99%
“…The resulting scrambled images resembled abstract patterns, rather than bodies. A similar technique was previously used to separate visual processing of biological motion from non-biological motion (Orgs et al, 2008). Sixteen pairs of body stimuli were used in the experiment, together with the 16 pairs of scrambled non-body images derived from them ( Figure 1 and Table 1 Supplementary Material).…”
Section: Stimulimentioning
confidence: 99%
“…Ballet dancers seeing Ballet movements and Capoeira dancers seeing Capoeira movements), compared to the other style (i.e Ballet dancers seeing Capoeira movements and vice versa). This study, together with others that have specifically used dance moves as a tool to evaluate the contribution of motor representations during action observation, have revealed the crucial role of a system that matches action execution and observation Cross et al, 2006;Orgs et al, 2008).…”
Section: Observing a Movementmentioning
confidence: 99%
“…Much of what we now know about the neural processing of movement is the result of this effort, which began with a TMS study showing motor resonance in the human motor cortex (Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995) and has grown to reach the level of a recent intracraneal cell recording study in humans (Mukamel, Ekstrom, Kaplan, Iacoboni, & Fried, 2010). The range of movements that have been used to investigate the neural mechanism of human movement perception in laboratory settings varies from simple hand actions (Grafton, et al, 1996;Grèzes, Costes, & Decety, 1999), to complex whole body movements such as dance movements (Calvo-Merino, Grèzes, Glaser, Passingham, & Haggard, 2006;Calvo-Merino, Glaser, Grèzes, Passingham, & Haggard, 2005;Cross, Hamilton, & Grafton, 2006;Orgs, Dombrowski, Heil, & Jansen-Osmann, 2008), including minimal representations of actions using point light displays (Saygin, Wilson, Hagler, Bates, & Sereno, 2004).…”
Section: Observing a Movementmentioning
confidence: 99%